Russia's agriculture: eight years in transition - convergence or divergence of regional efficiency - Vladimir Uvarovsky; Peter Voigt (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2000)
In this paper, we consider how Russian Agriculture has developed since the constitution of the Russian Federation. The analysis is based on Oblast level data of 75 territorial units during the period from 1993 to 1998 and is focusing on technical efficiency (TE), technological change, and (both aggregated as overall index) on Total Factor Productivity (TFP). Given that the initial natural conditions were approximately constant the consistence of political programs, market reforms and restructuring were essential determinants of regional developments of TE and TFP above or below the common trend. If this assumption is widely true an investigation of responsible circumstances for these divergences seems to be an important task in the actual regional-economic research. This paper should provide a step of such an analysis - discover common trends, make divergences visible and detect Oblasts characterised by diverging trends. The results have shown that the agricultural TE and the technological change varied dramatically among regions. Beyond it, we have found a growing gap of TE among regions and a relative homogeneous negative trend of technical change resulting, altogether, in a divergence of regional agricultural TFP. Because agriculture is for many regions the fundamental source of income this fact is alarming, especially when the local agriculture becomes noncompetitiveness in comparison with other regions, actually or in future. – – Gegenstand dieses Papiers ist die Entwicklung der russischen Landwirtschaft seit Gründung der Russischen Föderation. Die Analyse basiert auf regional aggregierten Daten von 75 Oblasts von 1993 bis 1998 und fokussiert auf die jeweilige technische Effizienz (TE), den technologischen Wandel und, als Aggregat, auf die totale Faktorproduktivität (TFP). Vorausgesetzt die regionalen natürlichen Bedingungen sind etwa gleich geblieben, dann sind die Konsistenz politischer Programme, marktwirtschaftliche Reformen und Restrukturierung die essentiellen Determinanten über- bzw. unterdurchschnittlicher Entwicklungen von TE und TFP. Wenn dies zutrifft, dann erscheint die Untersuchung der für die regionalen Divergenzen verantwortlichen Hintergründe als ein zentrales Ziel der aktuellen regional-ökonomischen Forschung. Dieses Papier soll hierzu einen Beitrag leisten allgemeine Trends offen legen, Divergenzen aufzeigen und Oblasts mit abweichenden Trends identifizieren. Die Ergebnisse zeigen erheblich differierende Werte sowohl bei der landwirtschaftlichen TE als auch beim technischen Wandel zwischen den einzelnen Regionen. Darüber hinaus kann man eine wachsende Disparität der TE bei einem relativ einheitlich negativen technischen Wandel feststellen, was insgesamt in eine zunehmende Divergenz der regionalen landwirtschaftlichen TFP mündet. Da die Landwirtschaft für viele Regionen die elementare Einkommensquelle darstellt, scheint dieses Faktum als durchaus alarmierend; insbesondere dann, wenn die lokale Landwirtschaft im regionalen Vergleich droht nicht mehr wettbewerbsfähig zu sein oder zu werden.
urn:nbn:de:gbv:3:2-22960
Keywords: O13; O47; 330; technical efficiency; rural areas; divergence; Russian Federation; agriculture; technische Effizienz; rurale Gebiete; Divergenz; Russland; Landwirtschaft; Landwirtschaft; Übergangswirtschaft; Technische Effizienz; Produktivität; Regionale Disparität; Schätzung; Russland